Assessment of the mesh refinement influence on the computed flow-fields about a model train in comparison with wind tunnel measurements. Issue 179 (August 2018) - Weinman, K.A.; Fragner, M.; Deiterding, R.; Heine, D.; Fey, U.; Braenstroem, F.; Schultz, B.; Wagner, C.
Abstract: A consistent mesh refinement study, relating to the prediction of aerodynamic forces about an experimentally validated reference train geometry, is presented in this paper. The flow about a high-speed train has a multi-scale character which poses challenges for the design of computationally effective meshes. The purpose of this study is to assist in the development of guidelines for effective drag prediction of high-speed trains using numerical simulation. These guidelines should assist CFD practitioners by identifying the regions of the mesh that are critical for the correct estimation of drag as well as providing information on appropriate mesh characteristics, such as volume and surface element length scales. Numerical assessments are validated against an experimental drag measurement program and the extent to which RANS is sufficiently predictive for industrial design is discussed. The results obtained in the work suggest that the mesh about the train nose is essential for the proper assessment of the aerodynamic drag acting on the vehicle. Highlights: A mesh refinement study is performed to assess mesh requirements for drag prediction about a train. CFD results are assessed against PIV and force measurements in a wind tunnel. Criterion for mesh design in the nose, underflow and wake regions are proposed. Mesh resolution about the nose region is critical for assessment of the vehicle drag.